2015
DOI: 10.1007/s11095-015-1752-9
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics of the CYP3A Substrate Midazolam in Morbidly Obese Patients Before and One Year After Bariatric Surgery

Abstract: PurposeBariatric surgery is nowadays commonly applied as treatment for morbid obesity (BMI > 40 kg/m2). As information about the effects of this procedure on a drug’s pharmacokinetics is limited, we aimed to evaluate the pharmacokinetics of CYP3A probe substrate midazolam after oral and intravenous administration in a cohort of morbidly obese patients that was studied before and 1 year post bariatric surgery.MethodsTwenty morbidly obese patients (aged 26–58 years) undergoing bariatric surgery participated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 47 publications
(51 reference statements)
9
81
1
1
Order By: Relevance
“…RYGBP was the predominant surgical procedure (n = 18) . In one study, BPD was investigated as the surgical procedure, while two studies investigated BPD‐DS, six studied SG, and one included jejunoileostomy …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RYGBP was the predominant surgical procedure (n = 18) . In one study, BPD was investigated as the surgical procedure, while two studies investigated BPD‐DS, six studied SG, and one included jejunoileostomy …”
Section: Resultsmentioning
confidence: 99%
“…Midazolam undergoes hydroxylation via both intestinal and hepatic CYP3A and is the most commonly used probe drug to investigate in vivo CYP3A activity . The effects on midazolam pharmacokinetics were explored in three of the studies that make up this systematic review . In one of these studies, absolute bioavailability and clearance were assessable because of a combined oral and intravenous administration of midazolam .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our pharmacokinetic evaluation, we noted a peak in norketamine at 60 min in the SDC rats, possibly justified by a possible saturation of the hepatic enzymes and most likely associated with a greater depth of anesthesia. Cytochrome P450 expression and function are influenced by obesity levels, such as CYP3A hepatic expression levels are increased in high-fat fed Sprague-Dawley rats [14], whereas decreased activity has previously been linked to obesity in humans [4]. In addition, liver transcriptomics analysis of mouse induced obesity models revealed a global dysregulation of Cyp genes, most notably in the Cyp3a and Cyp2c families [11].…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent matched cohort study from the same group showed that RYGB patients required higher doses of sedation during EGD than the non-RYGB with similar age, gender and BMI [31]. Authors hypothesized that these findings could be due to an improvement in liver function after gastric bypass, which resulted in an improvement in liver metabolism of fentanyl and midazolam, which subsequently led to increased requirement of both sedatives during EGD [3233]. …”
Section: Obesity and Sedationmentioning
confidence: 99%